Why is motilin active in some studies with mice, rats, and guinea pigs, but not in others? Implications for functional variability among rodents. Issue 2 (21st February 2022) - Sanger, Gareth J.
Abstract: The gastrointestinal (GI) hormone motilin helps control human stomach movements during hunger and promotes hunger. Although widely present among mammals, it is generally accepted that in rodents the genes for motilin and/or its receptor have undergone pseudonymization, so exogenous motilin cannot function. However, several publications describe functions of low concentrations of motilin, usually within the GI tract and CNS of mice, rats, and guinea pigs. These animals were from institute‐held stocks, simply described with stock names (e.g., "Sprague–Dawley") or were inbred strains. It is speculated that variation in source/type of animal introduces genetic variations to promote motilin‐sensitive pathways. Perhaps, in some populations, motilin receptors exist, or a different functionally‐active receptor has a good affinity for motilin (indicating evolutionary pressures to retain motilin functions). The ghrelin receptor has the closest sequence homology, yet in non‐rodents the receptors have a poor affinity for each other's cognate ligand. In rodents, ghrelin may substitute for certain GI functions of motilin, but no good evidence suggests rodent ghrelin receptors are highly responsive to motilin. It remains unknown if motilin has functional relationships with additional bioactive molecules formed from the ghrelin and motilin genes, or if a 5‐TM motilin receptor has influence in rodents (e.g., to dimerize with GPCRs and create different pharmacological profiles). Is the absence/presence of responses to motilin in rodents' characteristic for systems undergoing gene pseudonymization? What are the consequences of rodent supplier‐dependent variations in motilin sensitivity (or other ligands for receptors undergoing pseudonymization) on gross physiological functions? These are important questions for understanding animal variation.